Preparation of diglycolamide polymer modified silica and its application as adsorbent for rare earth ions - Zhe Liu; Yu Liu; Aijun Gong (Designed Monomers and Polymers, 2019)
Three novel diglycolamide monomers were synthesized and polymerized on silica. The diglycolamide polymer grafted silica were used as adsorbents for rare earth ions. The effects of acid concentration, structure of monomer, initial solution concentration, contact time and coexisting ions on adsorption of rare earth ions were investigated in detail. It was shown that the adsorption capacity increased with increasing acid concentration. Three adsorbents exhibited selectivity for middle and heavy rare earth over light rare earth in different extent. The adsorbent prepared from the monomer having the largest alkyl substituent showed the lowest adsorption capacity but the highest selectivity for different rare earth elements (REEs). Adsorption data were well fitted to the Langmuir isotherm and pseudo-second-order models. The presence of high concentrations (100 fold) of coexisting metal ions, K(I), Cr(II), Cu(II) or Fe(III), does not decrease the adsorption for rare earth ions seriously.